IBI Kosgoro 1957 Student Entrepreneurship Assistance to increase the Bubble Pearl Business Scale in Depok - Laksono, Rudi; Hasibuan, Ahmad Nurdin; Sundara, Dadan; Permatasari, Nova; Saidih, Renny (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
Community Service was carried out in the business activities of IBI Kosgoro 1957 students in the field of soft drinks in the form of Bubble drinks, located on Jl Arief Rahman Hakim No.64, Beji Depok, West Java. The program implemented by the team is in the form of an entrepreneurial concept based on business science. The activity was carried out with initial stages in the form of problem identification, needs analysis using the SWOT method, question and answer and observation and continued with counseling and assistance using the Business Model Canvas. Assistance activities are carried out in four stages, namely: Basic Management Assistance for SME management, Assistance in Preparation of Business Plans, Assistance in preparation of financial reports and Assistance for Access to Capital which aims to develop and increase business scale. number of students who wanted to become entrepreneurs increased to twenty percent.